Frequency of Antenatal Care: Does It Affect Pregnant Women's Anxiety in the Third Trimester?: A Cross-Sectional Study - Pamungkas, Indra Gilang; Dewi, Aliana; Pertiwi, Harizza; Setiawan, Heri (Faculty of Nursing and Midwifery, Binawan University, 2024)
Background: Antenatal Care (ANC) is a visit carried out by pregnant women to check the health status of their pregnancy. In Indonesia, 11 provinces have still not achieved the ANC visit target based on the Ministry of Health's 2017 Strategic Plan. The impact for pregnant women who do not make ANC visits is increased mortality and morbidity rates, undetected abnormalities, lack of information, and even anxiety. Method: This research uses a cross-sectional method. Spearman rank analysis was used to analyze data on 42 respondents at the Jatiasih District Health Center, Bekasi. Results: This study shows that there is a relationship between the frequency of ANC visits and anxiety of pregnant women in the third trimester with a p-value of 0.002 and r = 0.474. Conclusion: Pregnant women need to make ANC visits according to the regulations recommended by the government to protect their babies and their health status.